A educação infantil em Nova Hartz: da sua origem a novas possibilidades - Kohlrausch, Simone (Universidade do Vale do Rio do Sinos, 2006)
Looking for a research theme involves not just theoretical and empirical but also personal aspects. Seeing so many children being private of their right of being citizen, being child, being happy, in a so small city as Nova Hartz/RS I confronted myself with the questions of my project: Why one city relatively small, but with one high collection, invests so little in Infantile Education? Why the local public power silences in front of the necessities of the children? After all, who are the children of the city of Nova Hartz? What the city propitiates for the children? What it would have and what could offer? How is organized the Infantile Education in Nova Hartz? Why is it organized this way? Which elements of the local history elucidate us with this kind of organization? Which of the children are the chosen and which are not? To find the answers for these questions I developed a work with the following logic: conceptualization and the context of the childhood since the European source; the history of the chi
Keywords: história; Nova Hartz; políticas públicas; educação infantil; Ciências Humanas